2014
DOI: 10.1186/1472-6882-14-56
|View full text |Cite
|
Sign up to set email alerts
|

Questions about complementary and alternative medicine to the Regional Medicines Information and Pharmacovigilance Centres in Norway (RELIS): a descriptive pilot study

Abstract: BackgroundProvision of clinically relevant information about complementary and alternative medicine (CAM) to health care professionals is not well described. The aim of the study was to assess questions about CAM to the Regional Medicines Information and Pharmacovigilance Centres in Norway (RELIS).MethodsAll question-answers pairs (QAPs) in the RELIS database indexed with alternative medicine from 2005-2010 constituted the study material. A randomly selected sample of 100 QAPs was characterized with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…When a profession was described as alienated, a strong term for segregated from others, then it is time for a change in practices (Gandz, 2009). Research often demonstrated a high level of non-disclosure between patients and professions due to poor communication and lack of trust in the relationship (Kretchy et al, 2014;Schjott & Erdal, 2014;Skovgaard et al, 2014;Strouss et al, 2014). This has led to complications, side effects and mortality, when traditional or CAM treatments were mixed with conventional therapy due to lack of disclosure or dissatisfaction and unhappiness with conventional medicine (Gorski & Novella, 2014;Kretchy et al, 2014;McGregor et al, 2014;Schjott & Erdal, 2014;Skovgaard et al, 2014;Strouss et al, 2014).…”
Section: Respect and Communicationmentioning
confidence: 99%
See 4 more Smart Citations
“…When a profession was described as alienated, a strong term for segregated from others, then it is time for a change in practices (Gandz, 2009). Research often demonstrated a high level of non-disclosure between patients and professions due to poor communication and lack of trust in the relationship (Kretchy et al, 2014;Schjott & Erdal, 2014;Skovgaard et al, 2014;Strouss et al, 2014). This has led to complications, side effects and mortality, when traditional or CAM treatments were mixed with conventional therapy due to lack of disclosure or dissatisfaction and unhappiness with conventional medicine (Gorski & Novella, 2014;Kretchy et al, 2014;McGregor et al, 2014;Schjott & Erdal, 2014;Skovgaard et al, 2014;Strouss et al, 2014).…”
Section: Respect and Communicationmentioning
confidence: 99%
“…The researched demonstrated how current leadership and healthcare practices are failing the patients, employees, organizations, and communities (Avolio, 2007;Carey et al, 2011;Crosby, 2008;Gandz, 2009;Kretchy et al, 2014;;McGregor et al, 2014;Minke et al, 2006;Schjott & Erdal, 2014;Scott, 2010;Skovgaard et al, 2014;Strandberg et al, 2007;Strouss et al, 20 14;). Avolio (2007) reported that "the researchers need to stop underestimating the many potential elements" with regards to creating more integrative strategies in the area of leadership.…”
Section: Respect and Communicationmentioning
confidence: 99%
See 3 more Smart Citations